Intraguild predation by a European top predator – the Eagle Owl (Bubo bubo). - Lourenço, Rui (2012)
Intraguild predation (IGP) is common species interaction, which on several occasions can drive the structure of ecosystems. Although within vertebrate top predators, IGP seems less frequent, some studies have described this phenomenon. The Eagle Owl (Bubo bubo) is one of the most common avian top predators in Europe, and the possible interaction with endangered species is making conservationists consider the possibility of managing Eagle Owl populations. We present here a broad review of IGP by Eagle Owls 56 based on 41 studies with a complete report of diet for 44 study areas (68,774 prey)